Comparative Study of Biodiesel Blends Derived from Vegetable Oils: Properties Investigation - Ahmed, Md. Rafi; Nazrul, Nasif Bin; Ahammed, Md Sazib; Siddike, Md Abubakker; Islam, K. M. Oajedul (SciEn Conference Series: Engineering, 2025)
This study investigates the fuel properties of biodiesel blends derived from coconut, soybean, and mustard oils, aiming to provide sustainable alternatives to conventional diesel. The research addresses the growing need for eco-friendly fuel options with improved performance and reduced emissions. Individual biodiesels exhibited densities (0.87–0.91 g/mL) and calorific values (39.883–40.558 kJ/g) slightly varying from mineral diesel (0.83 g/mL and 45.727 kJ/g). Blending these biodiesels in equal proportions led to a density reduction to 0.801 g/mL and an enhanced calorific value of 41.895 KJ/g, indicating potential for improved fuel performance. Samples were prepared using the transesterification method and blending techniques. The fuel properties, such as density, calorific value, and flash point, were then analyzed. Among the tested blends, the coconut + soybean + mustard + mineral diesel (1:1:1:1.5) blend show higher calorific value and effectively optimizing fuel properties, which ensures maintaining safety in handling. Additionally, this blend achieved a density enhancement to 0.781 g/mL and a calorific value elevation to 42.977 kJ/g, closely resembling pure diesel properties. Flash point analysis ranges between 121°C and 156°C when blended that highlights the importance of safety in fuel handling and combustion. The findings highlight the probable ability of multi-feedstock biodiesel blends to reduce harmful emissions, including CO and particulate matter, while ensuring adequate combustion performance. This study shows the feasibility of biodiesel blends as environmentally friendly alternatives to traditional fossil fuels, also emphasize their role to achieve energy sustainability and addressing the global energy crisis.